RUSSIA’S WAR ON UKRAINE - Bela, Valon; Ruzin, Nano; İdrizi, Zeqirja (International Scientific Journal Vision, 2025)
Russia’s war on Ukraine, which began in earnest with the invasion on February 24, 2022, is one of the most significant and tragic events in modern European history. This conflict, rooted in complex historical, political, and cultural dynamics, has led to a humanitarian catastrophe, destabilized global geopolitics, and raised fundamental questions about international law and order. In this essay, we will explore the origins of the conflict, the key events that have shaped it, the motivations behind Russia’s actions, the response from Ukraine and the international community, and the broader implications of the war.